Chronic illness and extreme performance: Type 1 diabetes in ultra-endurance - Jean-Charles Vauthier; Lucie Choley; Bernard Kabuth (PLoS ONE, 2025)
Background This study explores how people with type 1 diabetes experience ultra-endurance sports, focusing on identity, self-management, and psychosocial impacts through a qualitative approach. Methods and findings This qualitative study used a constructivist grounded theory approach. Thirteen semi-structured interviews were conducted with French-speaking adults living with T1D who had completed at least one marathon or ultra-endurance race. Data were analyzed inductively through line-by-line coding, focused coding, and thematic categorization, supported by NVivo® software and reported in accordance with COREQ guidelines. Four major themes emerged: (1) a progressive process of acceptance, from the shock of diagnosis to identity integration; (2) the ambivalence of being “ill,” with tensions between medical status and personal identity; (3) the mental load of diabetes management, intensified by ultra-endurance but mitigated by adaptive strategies and peer support; and (4) sport as a transformative space for self-affirmation, resilience, and advocacy. Participants described how ultra-endurance helped them reclaim agency, reframe their illness, and inspire others. Conclusions Ultra-endurance sports offer a unique context for identity reconstruction and empowerment among people with T1D. Far from being a barrier, the illness can become a driver of personal growth and social visibility. These findings highlight the importance of recognizing experiential knowledge in chronic disease management and call for more inclusive, patient-centered approaches in healthcare and research.